TINJAUAN KRIMINOLOGI TERHADAP KEJAHATAN PENCURIAN DENGAN KEKERASAN (STUDI KASUS DI WILAYAH HUKUM KEPOLISIAN RESOR KUPANG) - Selan, Sari Angelina Ribka; Manafe, Deddy R. CH; Djara Dima, Adrianus (Petitum Law Journal, 2023)
This research uses empirical legal research methods using a case approach. The data sources used are primary, secondary data, and the technical data analysis carried out is descriptive qualitative. The results of this research can be seen that (1). Factors that cause violent theft are: (a). economic factors, (b). environmental factors, (c). Internal factors. (2). The public's reaction to the crime of theft with violence is fear, anxiety, ostracism from society towards the perpetrator, and ridicule. (3). The countermeasures carried out by the Kupang Police are repressive. It is recommended that the public become more familiar with the surrounding environment, especially interactions between fellow citizens and especially people they have just met. Also for the Police and the Government to work together in tackling violent crimes of theft that occur in society so as to create a sense of security and peace for people's lives.